2022
DOI: 10.1017/jfm.2022.405
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of unsteady effects in oscillatory sheet flows

Abstract: In this paper, two-phase flow simulations of oscillatory sheet flow experimental configurations involving medium and fine sand using a turbulence-resolving two-fluid model are presented. The turbulence-resolving two-phase flow model reproduces the differences of behaviour observed between medium and fine sand whereas turbulence-averaged models require an almost systematic tuning of empirical model coefficients for turbulence–particle interactions. The two-fluid model explicitly resolves these interactions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Simulations are conducted with the open-source software SedFoam, a two-phase flow solver used for sediment transport applications (Chassagne, Bonamy, & Chauchat, 2023; Chauchat et al, 2017; Mathieu, Chauchat, Bonamy, & Nagel, 2019; Mathieu, Cheng, Chauchat, Bonamy, & Hsu, 2022; Montellà et al, 2021; Tsai, Mathieu, Montellà, Hsu, & Chauchat, 2022) based on the open-source finite volume library OpenFOAM (Jasak & Uroić, 2020) (v2212 release from ESI). The solver is available for download from GitHub ().…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Simulations are conducted with the open-source software SedFoam, a two-phase flow solver used for sediment transport applications (Chassagne, Bonamy, & Chauchat, 2023; Chauchat et al, 2017; Mathieu, Chauchat, Bonamy, & Nagel, 2019; Mathieu, Cheng, Chauchat, Bonamy, & Hsu, 2022; Montellà et al, 2021; Tsai, Mathieu, Montellà, Hsu, & Chauchat, 2022) based on the open-source finite volume library OpenFOAM (Jasak & Uroić, 2020) (v2212 release from ESI). The solver is available for download from GitHub ().…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…The interaction between this damping and the turbulent resuspension and transport of muddy sediment is not yet fully understood, but recent research has indicated a strong relationship between small scale turbulence in the bottom boundary layer and the movement of fine muddy sediment [14,15]. Two-phase modeling has been used to show that the boundary layer thickness of fine sediment suspension is increased by the complex interplay between flow instabilities, stress terms, and sediment-induced turbulence attenuation [16]. It is worthwhile to mention the processes of erosion within the context of the rheological behavior of the dense muddy mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…An example is the model by Bakhtyar et al (2010), who applied this technique to simulate small-scale swash zone dynamics under regular waves. This technique was also used by Mathieu et al (2022) for modelling detailed sediment and turbulence interactions in the sheet flow layer. Although these models include more physics, the major downside is their relative computational inefficiency.…”
Section: Research and Model Approachesmentioning
confidence: 99%